(untitled) (Altre Modernità, 2024)
Focusing on the analysis of the movies and the TV series created by Brit Marling with some recurring collaborators (Sound of my Voice [2011], Another Earth [2011], The East [2013], The OA [2016-2019]), the article proposes an interpretation of the author’s work within the context of an intersectional spiritual ecofeminism recognizable in in her poetics, highlighting its connection to some of the most relevant movements of the 2010s – feminists, environmentalists, and against systemic violence. While Marling’s narratives always revolve around imminent catastrophes, different forms of violence, and humanity’s role in the fate of the Earth, the message that emerges from these texts is always oriented towards the search for alternative ways to create interconnections and new possible futures. It is not only accurate to refer to Marling’s work as an engaged poetics, but the reception of her work too has involved an activist dimension: the sequence of movements that in The OA embodies the strength of the intersubjective bond between the characters has been integrated into various flashmobs, one of the most participated took place in August 2017 at the Trump Tower in New York to protest against the administration in power.